Corporate Social Responsibility in Peru. Reality vs Speech - León Untiveros, Miguel A. (2010)
In Peru, the awareness of corporate social responsibility (CSR), at least at the level of discourse, occupies a significant space. Therefore, it is extremely important to evaluate its implementation in view of its economic and social reality. Thus, in this paper the state of the art is presented along with some important criticisms of CSR and its broader notion: corporate sustainability (parts I to IV). For this reason, the author throughout the text will explore different definitions of CSR that encompass various mathematical formulations used in economics. Added to this, it will refer to the concepts held by Professor Francisco Durand regarding the different economies in Peru. Then, the discursive model is contrasted with the Peruvian reality to conclude that, as things are, the only model of corporate social responsibility is the Friedmannian one (profitability).